Balaclava boy - Robson, Jenny ca. 20./21. Jh (Tafelberg, 2011)
"When the headmaster presents Tommy McAdam to his new classmates in Grade Four at Colliery Primary they are especially interested to find out more about him - the usual things: where he's from, what sports he plays - but most of all, why does he refuse to take off his balaclava? They begin to like him despite of the balaclava, which he wears to school religiously - a different colour each day. He is a great soccer player and fits right in with the other boys. Of course their curiosity grows, and eventually they think of a plan to reveal Tommy's secret. The line drawings are by Sandy Mitchell, a freelance artist from Kalk Bay, Cape Town. This book is great fun, and readers won't guess the secret until the very end!"--Publisher's website